Influence of Surfactant Bilayers on the Refractive Index Sensitivity and Catalytic Properties of Anisotropic Gold Nanoparticles. Issue 3 (19th November 2015) - Martinsson, Erik; Shahjamali, Mohammad M.; Large, Nicolas; Zaraee, Negin; Zhou, Yu; Schatz, George C.; Mirkin, Chad A.; Aili, Daniel
Abstract : Shape‐controlled synthesis of gold nanoparticles generally involves the use of surfactants, typically cetyltrimethylammonium (CTAX, X = Cl −, Br − ), to regulate the nucleation growth process and to obtain colloidally stable nanoparticles. The surfactants adsorb on the nanoparticle surface making further functionalization difficult and therefore limit their use in many applications. Herein, the influence of CTAX on nanoparticle sensitivity to local dielectric environment changes is reported. It is shown, both experimentally and theoretically, that the CTAX bilayer significantly reduces the refractive index (RI) sensitivity of anisotropic gold nanoparticles such as nanocubes and concave nanocubes, nanorods, and nanoprisms. The RI sensitivity can be increased by up to 40% by removing the surfactant layer from nanoparticles immobilized on a solid substrate using oxygen plasma treatment. This increase compensates for the otherwise problematic decrease in RI sensitivity caused by the substrate effect. Moreover, the removal of the surfactants both facilitates nanoparticle biofunctionalization and significantly improves their catalytic properties. The strategy presented herein is a simple yet effective universal method for enhancing the RI sensitivity of CTAX‐stabilized gold nanoparticles and increasing their potential as transducers in nanoplasmonic sensors, as well as in catalytic and biomedical applications. Abstract : Increased refractive index sensitivity, improved biofunctionalization, and catalytic activity of anisotropic gold nanoparticles stabilized by surfactants are reported using a simple yet effective method based on oxygen plasma treatment. The findings open up new opportunities for the design, and optimization of nanostructures that are important in the development of high precision nanoplasmonic‐based biosensors and other biomedical devices.